"Na drugim planie". Nierzymskokatolickie Kościoły i związki wyznaniowe na obrzeżach głównego nurtu polityki wyznaniowej PRL = "In the Background". Non-Roman-Catholic Churches and Religious Associations on the Outskirts of the Mainstream Religious Policy of the PRP - Michalak. Ryszard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The intention and strategic aim of the party and national authorities in the People?s Republic of Poland was to eradicate all religious organizations (with the Roman Catholic church as their main target) and the complete cessation of religious life. In practice, the eradication policy meant regular, repressive action against the two religious associations in the years 1945-1989 (the Greek Orthodox Church and Jehovah?s Witnesses) and four other in the years 1945-1956 (the Methodist Church, the United Evangelical Church, the Union of Churches of Seventh-day Adventists, the Polish-Catholic Church).
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia